Algebraization in stability problem for stationary waves of the Klein-Gordon equation - Goloskubova, Nataliia; Mikhlin, Yuri V. (Харківський національний університет імені В. Н. Каразіна, 2019)
Nonlinear traveling waves of the Klein-Gordon equation with cubic nonlinearity are considered. These waves are described by the nonlinear ordinary differential equation of the second order having the energy integral. Linearized equation for variation obtained for such waves is transformed to the ordinary one using separation of variables. Then so-called algebraization by Ince is used. Namely, a new independent variable associated with the solution under consideration is introduced to the equation in variations. Integral of energy for the stationary waves is used in this transformation. An advantage of this approach is that an analysis of the stability problem does no need to use the specific form of the solution under consideration. As a result of the algebraization, the equation in variations with variable in time coefficients is transformed to equation with singular points. Indices of the singularities are found. Necessary conditions of the waves stability are obtained. Solutions of the variational equation, corresponding to boundaries of the stability/instability regions in the system parameter space, are constructed in power series by the new independent variable. Infinite recurrent systems of linear homogeneous algebraic equations to determine coefficients of the series can be written. Non-trivial solutions of these systems can be obtained if their determinants are equal to zero. These determinants are calculated up to the fifth order inclusively, then relations connecting the system parameters and corresponding to boundaries of the stability/ instability regions in the system parameter place are obtained. Namely, the relation between parameters of anharmonicity and energy of the waves are constructed. Analytical results are illustrated by numerical simulation by using the Runge-Kutta procedure for some chosen parameters of the system. A correspondence of the numerical and analytical results is observed.

Розглянуто нелінійні бігучі хвилі рівняння Клейна-Гордона з кубічною нелінійністю. Ці хвилі описуються звичайним диференціальним рівнянням другого порядку, що має інтеграл енергії. Лінеарізоване рівняння у варіаціях для таких хвиль трансформується у звичайне диференціальне рівняння за допомогою розподілення змінних. Потім використовується так звана алгебраізація за Айнсом. А саме, у рівняння в варіаціях вводиться нова незалежна змінна, що пов’язана з рішенням, яке розглядається. Під час такої трансформації використовується інтеграл енергії для стаціонарних хвиль. Перевага такого підходу зв’язана з тим, що для аналізу проблеми стійкості не треба dикористовувати специфічний вигляд рішення, що розглядається. В результаті такої алгебраізації рівняння у варіаціях зі змінними за часом коефіцієнтами перетворюється у рівняння з особливими точками. Знайдено індекси особливих точок. Отримано необхідні умови стійкості хвиль. Рішення рівнянь у варіаціях, що відповідають межам регіонів стійкості / нестійкості в просторі параметрів системи побудовано у вигляді степеневих рядів за новою незалежною змінною. Можуть бути виписані нескінченні рекурентні системи алгебраїчних рівнянь для розрахунку коефіцієнтів цих рядів. Нетривіальні розв’язки таких систем можуть бути отримані, якщо їх визначники дорівнюють нулю. Ці визначники розраховано до п’ятого порядку включно, а потім отримано зв’язки між параметрами системи і відповідні межі регіонів стійкості/ нестійкості в площині параметрів системи. А саме, встановлено зв’язки між параметрами ангармонізму та енергії хвилі. Аналітичні результати проілюстровано чисельним моделюванням за допомогою процедури Рунге-Кутти. Спостерігається відповідність чисельних та аналітичних результатів.

Рассмотрены нелинейные бегущие волны уравнения Клейна-Гордона с кубической нелинейностью. Эти волны описываются обыкновенным дифференциальным уравнением второго порядка, которое имеет интеграл энергии. Линеаризованное уравнение в вариациях для таких волн преобразуется в обыкновенное дифференциальное уравнение при помощи разделения переменных. Затем используется так называемая алгебраизация по Айнсу. А именно, новая независимая переменная, которая связана с решением, которое рассматривается, вводится в уравнение в вариациях. При этом используется интеграл энергии для стационарных волн. Преимущество такого подхода состоит в том, что для анализа проблемы устойчивости не нужно использование специфической формы решения, которое рассматривается. В результате подобной алгебраизации уравнение в вариациях с переменными по времени коэффициентами преобразуется в уравнение с особыми точками. Найдены индексы особых точек. Решения уравнений в вариациях, которые отвечают границам областей устойчивости/неустойчивости, построены в виде степенных рядов по новой независимой переменной. Могут быть выписаны бесконечные рекуррентные системы алгебраических уравнений для определения коэффициентов этих рядов. Нетривиальные решения таких систем могут быть получены, если их определители равны нулю. Эти определители вычисляются до пятого порядка включительно, затем зависимости между параметрами системы и соответствующие границы областей устойчивости/неустойчивости были получены. А именно, установлены связи между параметрами ангармонизму и энергии волны. Аналитические результаты иллюстрируются численным моделированием при помощи процедуры Рунге-Кутты. Наблюдается соответствие численных и аналитических результатов.
Алгебраізація в задачі стійкісті стаціонарних хвиль рівняння Клейна-Гордона
Алгебраизация в задаче устойчивости стационарных волн уравнения Клейна-Гордона с кубической нелинейностью
Keywords: the Klein-Gordon equation; stationary waves stability; Ince algebraization; рівняння Клейна-Гордон; стійкість стаціонарних хвиль; алгебраізація за Айнсом; уравнения Клейна-Гордона; устойчивость стационарных волн; алгебраизация по Айнсу